2022
DOI: 10.1111/1467-8454.12253
|View full text |Cite
|
Sign up to set email alerts
|

Re‐examining the impact of sectoral‐ and industrial‐level FDI on growth: Does institutional quality, education levels and trade openness matter?

Abstract: This study examines whether institutional quality, education levels and trade openness affect the relationship between sectoral‐ and industrial‐level foreign direct investment (FDI) inflows and economic growth. Previous studies highlight the heterogeneous effects of FDI at the sectoral‐ and industrial‐level suggesting the need to examine the growth effects of FDI at a disaggregated level. However, previous studies have not empirically explored the role of absorptive capacities at the industrial‐ and sectoral‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…This paper aims to investigate the effect of sector‐specific FDI inflows in host countries (MENA countries) on growth at both the aggregate and sectoral levels. We estimate the following dynamic model, similar to (Doytch, 2021; Doytch & Uctum, 2011, 2019; Gönel & Aksoy, 2016; Haini & Tan, 2022): Yi,tk=normalα0+normalα1Yi,t1k+normalα2FDIi,ts+normalα3Xi,t+μi+δt+εi,t, where Yi,tk is real per capita growth output in sector k in the constant year 2010 USD {the ‘ k ’ superscript corresponds to any one of agriculture, mining, manufacturing, services sectors as well as aggregate GDP}, FDIi,ts refers to FDI flows as a percentage of GDP {the ‘ s ’ superscript corresponds to the primary, secondary and tertiary sectors, as well as the total FDI} (according to the International Standard Industry Classification [ISIC], we categorised FDI inflows into the following economic sectors: primary [including petroleum and mining], secondary [including food, fabricated metals, chemical, electrical, industrial machinery and transportation equipment] and tertiary [comprising depository institutions (financial institutions, commonly referred to as ‘depository institutions’ in the United States) and wholesale trade]). For more detailed information regarding this classification, we recommend referring to the study conducted by Doytch et al (2015), Xi,t is a vector of other variables in country i at period t , which are {IQ, investment rate, school, trade openness, natural resource rent as a share of GDP, and government spending}, μi denotes country‐fixed effects that capture unobservable heterogeneity across different countries in the analysis, δt denotes time‐fixed effects represented by year dummies that capture common shocks to a dependent variable for all countries.…”
Section: Empirical Model Data and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…This paper aims to investigate the effect of sector‐specific FDI inflows in host countries (MENA countries) on growth at both the aggregate and sectoral levels. We estimate the following dynamic model, similar to (Doytch, 2021; Doytch & Uctum, 2011, 2019; Gönel & Aksoy, 2016; Haini & Tan, 2022): Yi,tk=normalα0+normalα1Yi,t1k+normalα2FDIi,ts+normalα3Xi,t+μi+δt+εi,t, where Yi,tk is real per capita growth output in sector k in the constant year 2010 USD {the ‘ k ’ superscript corresponds to any one of agriculture, mining, manufacturing, services sectors as well as aggregate GDP}, FDIi,ts refers to FDI flows as a percentage of GDP {the ‘ s ’ superscript corresponds to the primary, secondary and tertiary sectors, as well as the total FDI} (according to the International Standard Industry Classification [ISIC], we categorised FDI inflows into the following economic sectors: primary [including petroleum and mining], secondary [including food, fabricated metals, chemical, electrical, industrial machinery and transportation equipment] and tertiary [comprising depository institutions (financial institutions, commonly referred to as ‘depository institutions’ in the United States) and wholesale trade]). For more detailed information regarding this classification, we recommend referring to the study conducted by Doytch et al (2015), Xi,t is a vector of other variables in country i at period t , which are {IQ, investment rate, school, trade openness, natural resource rent as a share of GDP, and government spending}, μi denotes country‐fixed effects that capture unobservable heterogeneity across different countries in the analysis, δt denotes time‐fixed effects represented by year dummies that capture common shocks to a dependent variable for all countries.…”
Section: Empirical Model Data and Methodologymentioning
confidence: 99%
“…Since our sample dataset is based on a sample of 13 MENA countries from 2000 to 2020, panel estimators are suitable for the study. Due to the dynamic nature of FDI and economic growth in its data‐generating process, it might be possible that endogeneity and simultaneity exist (Haini & Tan, 2022; Iamsiraroj, 2016; Li & Liu, 2005). It has been demonstrated that good institutions may promote FDI, with human capital increasing FDI in the service sector and good institutions attracting FDI in the manufacturing sector (Ahmad et al, 2018; Doytch & Eren, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a critical determinant of FDI inflows in the economy, the support and availability of skilled manpower have emerged as a motivation for foreign investors to transfer technology and operation processes in the form of capital. In terms of empirical association, a growing number of studies have posted the beneficial role of education in inducing foreign investors in the host economy [ 27 , [49] , [50] , [51] , [52] ]. For instance, Su, Jiang [ 53 ] considering the provincial data, investigated the effect of environmental investment in higher education on FDI and established positive and statistically significant linkage in the long run.…”
Section: Literature Survey and Hypothesis Developmentmentioning
confidence: 99%